The Effectiveness of Imposing the Death Penalty for Corruption Perpetrators as a Solution for Handling Corruption during the Covid-19 Pandemic - Marisa Kurnianingsih; M. Zaki Attirmidzi (Universitas Muhammadiyah Surakarta, 2021)
The first objective of this study is to determine the extent to which the government has made efforts to prevent and eradicate corruption, the second is to determine the effectiveness of the imposition of the death penalty for corruption perpetrators as a solution for handling corruption during the Covid-19 pandemic. This study uses a juridical-normative approach where the main data source is secondary data in the form of written materials about the law which are then analyzed quantitatively with the aim of producing descriptive analytical data. From this research, it is found that efforts to prevent and eradicate the criminal act of corruption in Indonesia are carried out through prevention and prosecution efforts. Indonesia has entered the state level in a state of danger as regulated in the explanation of Article 2 subsection (2) of the Law on criminal act of corruption regarding certain circumstances due to various kinds of policies issued by the government regarding the Covid-19 pandemic, so that the implementation of the death penalty for corruption perpetrators, especially in the Covid-19 pandemic situation, has a preventive effect on public officials who will commit corruption.